Disentangling the Relative Drivers of Seasonal Evapotranspiration Across a Continental‐Scale Aridity Gradient. Issue 8 (10th August 2022) - Young, Adam M.; Friedl, Mark A.; Novick, Kimberly; Scott, Russell L.; Moon, Minkyu; Frolking, Steve; Li, Xiaolu; Carrillo, Carlos M.; Richardson, Andrew D.
Abstract: Evapotranspiration ( ET ) is a significant ecosystem flux, governing the partitioning of energy at the land surface. Understanding the seasonal pattern and magnitude of ET is critical for anticipating a range of ecosystem impacts, including drought, heat‐wave events, and plant mortality. In this study, we identified the relative controls of seasonal variability in ET, and how these controls vary among ecosystems. We used overlapping AmeriFlux and PhenoCam time series at a daily timestep from 20 sites to explore these linkages (# site‐years >100), and our study area covered a broad climatological aridity gradient in the U.S. and Canada. We focused on disentangling the most important controls of bulk surface conductance ( G s ) and evaporative fraction ( EF = LE /[ H + LE ]), where LE and H represent latent and sensible heat fluxes, respectively. Specifically, we investigated how vegetation phenology varied in importance relative to meteorological variables (vapor pressure deficit and antecedent precipitation) as a driver of G s and EF using path analysis, a framework for quantifying and comparing the causal linkages among multiple response and explanatory variables. Our results revealed that the drivers of G s and EF seasonality varied significantly between energy‐ and water‐limited ecosystems. Specifically, precipitation had a much higher effect in water‐limited ecosystems, while seasonal patterns in canopy greenness emerged as a stronger control in energy‐limited ecosystems. Given that phenology is expected to shift under future climate, our findings provide key information for understanding and predicting how phenology may impact 21st‐century hydroclimate regimes and the surface‐energy balance. Plain Language Summary: Surface‐to‐atmosphere water fluxes (i.e., evapotranspiration) are an important dynamic of terrestrial ecosystems, influencing the timing and severity of impacts such as drought, heat‐wave events, and plant mortality. In this study, we explored why seasonal variability in evapotranspiration ( ET ) varies among a wide range of ecosystems. To conduct this work, we used AmeriFlux and PhenoCam datasets, which measure daily meteorological conditions and canopy greenness, respectively, from 20 individual sites. Our study area covered a broad climatological aridity gradient in the US and Canada, spanning from deciduous forests ecosystems in the northeast to drylands in the southwest. The most important finding from this work was that reoccurring patterns in vegetation green‐up and senescence (i.e., phenology) consistently emerged as one of the strongest predictors of ET in ecosystems where water was non‐limiting. By comparison, seasonal patterns in precipitation were identified as the strongest control of ET seasonality in dryland ecosystems where water is considerably scarcer, and phenology had much weaker influence in these regions. Overall, this study provides key insight into the sensitivity of ET seasonality to various drivers and ecosystem water availability. Key Points: In terrestrial ecosystems of North America, evapotranspiration ( ET ) displays strong seasonal patterns Path analysis was used to explore how the drivers of ET seasonality vary among different ecosystems and hydroclimate regimes Phenology emerged as the best predictor of ET in energy‐limited regions; precipitation had a higher effect in water‐limited ecosystems